Ovine Mesenchymal Stromal Cells: Morphologic, Phenotypic and Functional Characterization for Osteochondral Tissue Engineering. - Clara Sanjurjo-Rodríguez; Rocío Castro-Viñuelas; Tamara Hermida-Gómez; Tania Fernández-Vázquez; Isaac Manuel Fuentes-Boquete; Francisco Javier de Toro-Santos; Silvia María Díaz-Prado; Francisco Javier Blanco-García (PLoS ONE, 2017)
Introduction Knowledge of ovine mesenchymal stromal cells (oMSCs) is currently expanding. Tissue engineering combining scaffolding with oMSCs provides promising therapies for the treatment of osteochondral diseases. Purpose The aim was to isolate and characterize oMSCs from bone marrow aspirates (oBMSCs) and to assess their usefulness for osteochondral repair using β-tricalcium phosphate (bTCP) and type I collagen (Col I) scaffolds. Methods Cells isolated from ovine bone marrow were characterized morphologically, phenotypically, and functionally. oBMSCs were cultured with osteogenic medium on bTCP and Col I scaffolds. The resulting constructs were evaluated by histology, immunohistochemistry and electron microscopy studies. Furthermore, oBMSCs were cultured on Col I scaffolds to develop an in vitro cartilage repair model that was assessed using a modified International Cartilage Research Society (ICRS) II scale. Results oBMSCs presented morphology, surface marker pattern and multipotent capacities similar to those of human BMSCs. oBMSCs seeded on Col I gave rise to osteogenic neotissue. Assessment by the modified ICRS II scale revealed that fibrocartilage/hyaline cartilage was obtained in the in vitro repair model. Conclusions The isolated ovine cells were demonstrated to be oBMSCs. oBMSCs cultured on Col I sponges successfully synthesized osteochondral tissue. The data suggest that oBMSCs have potential for use in preclinical models prior to human clinical studies.